2020
DOI: 10.1080/15568318.2020.1818330
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of electric vehicles: Which factors are really important?

Abstract: Electric vehicles stand out for their ability to reduce pollution. However, electric vehicle sales have not been brisk despite their positive effects. The objective of this study is twofold: first, to determine the variables that predict the purchase of an electric vehicle from the implementation of an algorithm based on computational intelligence; second, to contrast these results with two panels of experts in consumer behavior and the automobile sector. An empirical study was carried out with 404 potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 92 publications
(130 reference statements)
4
38
2
Order By: Relevance
“…Furthermore, three extracted marketing characteristics, including "cheaper electricity tariff," "cheaper maintenance fee," and "a cost-effective price of car payment, " can be categorized as the vehicle subsystem [10] and make an "affordable" impression on consumers; then, the last one is the most crucial among other design characteristics. In addition, both "friendly" and "affordable" impressions can be viewed as incentives that are the reliable predictors of purchase intention of EVs [20]. Then, "Having the function of autopilot" and "having the technique of Internet of vehicles" belong to electronic onboard subsystem [10], "constructing a live circle of pure electric" and "government subsidies" are next and vests in the "infrastructure subsystem [10]; then, "Having the technique of Internet of vehicles" and "government subsides" are more important than the other marketing characteristics and make consumers feel "intelligent" and "affordable individually."…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, three extracted marketing characteristics, including "cheaper electricity tariff," "cheaper maintenance fee," and "a cost-effective price of car payment, " can be categorized as the vehicle subsystem [10] and make an "affordable" impression on consumers; then, the last one is the most crucial among other design characteristics. In addition, both "friendly" and "affordable" impressions can be viewed as incentives that are the reliable predictors of purchase intention of EVs [20]. Then, "Having the function of autopilot" and "having the technique of Internet of vehicles" belong to electronic onboard subsystem [10], "constructing a live circle of pure electric" and "government subsidies" are next and vests in the "infrastructure subsystem [10]; then, "Having the technique of Internet of vehicles" and "government subsides" are more important than the other marketing characteristics and make consumers feel "intelligent" and "affordable individually."…”
Section: Discussionmentioning
confidence: 99%
“…The battery life, purchase cost, driving range, and charging times were considered product-level factors [20]. Higueras-Castillo et al (2021) studied product factors like minimum range, charging time, low noise, acceleration, and context factors like price, perceived benefit, incentives, and infrastructure [21]. Higueras-Castillo et al (2021) surveyed 404 prospective EV consumers in Spain about their beliefs, EV attitudes, and purchase intention towards EVs [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higueras-Castillo et al (2021) studied product factors like minimum range, charging time, low noise, acceleration, and context factors like price, perceived benefit, incentives, and infrastructure [21]. Higueras-Castillo et al (2021) surveyed 404 prospective EV consumers in Spain about their beliefs, EV attitudes, and purchase intention towards EVs [21]. Their research findings reveal that driving range, government incentives, and reliability are the most important predictors of purchase intention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The average price point of $3100, charging time of 35 min, and vehicle driving range of 401 KM were identified as the tipping points to achieve mainstream EV adoption in India [ 22 ]. Higueras-Castillo et al [ 23 ] in their study to find factors that affect electric vehicle purchase intentions in Spain conclude that driving range, financial incentives, and vehicle reliability are the most important predictors of the purchase intention. Bennett and Vijaygopal [ 24 ] found that a weak link exists between attitude and willingness to purchase an electric vehicle.…”
Section: Introductionmentioning
confidence: 99%